2011
DOI: 10.1097/coc.0b013e3181e8461a
|View full text |Cite
|
Sign up to set email alerts
|

Selective Serotonin Reuptake Inhibitors, Glioblastoma Multiforme, and Impact on Toxicities and Overall Survival

Abstract: This retrospective review suggests that concomitant use of an SSRI during treatment does not adversely affect survival. There was no increased toxicity with the use of SSRI concurrent with treatment of newly-diagnosed GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 7 publications
2
42
0
Order By: Relevance
“…Previous clinical trials indicated that paroxetine and citalopram markedly improved cancer patients' quality of life [37, 38]. Additionally, a retrospective review suggested that using SSRI antidepressants, including citalopram, escitalopram, fluoxetine, fluvoxamine, paroxetine, and sertraline, for glioma treatment did not adversely affect survival rates [39]. Based on those studies, we attempted to identify which SSRI antidepressants could be potentially used for treating glioma cells and studied the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical trials indicated that paroxetine and citalopram markedly improved cancer patients' quality of life [37, 38]. Additionally, a retrospective review suggested that using SSRI antidepressants, including citalopram, escitalopram, fluoxetine, fluvoxamine, paroxetine, and sertraline, for glioma treatment did not adversely affect survival rates [39]. Based on those studies, we attempted to identify which SSRI antidepressants could be potentially used for treating glioma cells and studied the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Retrospective data further suggest that selective serotonin reuptake inhibitor (SSRI) antidepressants may be safe in glioma. In one large case notes review (n=160), there was no evidence of increased toxicity among patients with glioblastoma multiforme taking an SSRI 64. These and other retrospective studies are reassuring,52 65 but the potential risks of prescribing antidepressants in glioma justify prospective studies 66…”
Section: Unanswered Questionsmentioning
confidence: 95%
“…However, a subsequent case–control retrospective study by the same group found no association between tricyclic antidepressant (TCA) prescription and all-cause mortality following glioma diagnosis 73. A retrospective case-note review suggested, by contrast, that GBM patients who received an SSRI had a reduced risk of death in the first 2 years postoperatively 64. Prospective case–control studies are warranted to explore these interesting but contradictory findings.…”
Section: Unanswered Questionsmentioning
confidence: 99%
“…However, there are little data on the use of antidepressants in this patient population. In order to investigate selective serotonin reuptake inhibitors (SSRIs) and their impact on toxicities and survival in patients with GBM, a review was performed on data from 160 patients from 1999 to 2008 [50]. A majority of the patients received temozolomide and radiation, and 21.8% of patients overall received SSRIs during initial therapy.…”
Section: Seizure Control -Implications For the Pharmacistmentioning
confidence: 99%